(untitled) (Journal of Comparative Social Work, 2010)
Social work education is rapidly developing in the Socialist Republic of Vietnam and it is facing new challenges as it blends the historical, political and cultural influences. This article reviews and compares the historical and recent developments of social work in Canada and Vietnam. Canadian social work developed in Euro-western culture and its values, whereas, Vietnam suffered under French colonialism, a 30 year war of independence and then economic depression. For many years, social work remained nebulous but in recent years, the country has seen a rebirth of social work. Field education is the link from theory to practice and is often where differences between the two countries become evident. The article concludes with a discussion on the professionalization of social work and its future contribution to the emerging “new” Vietnam.